PENGARUH GROWTH OPPORTUNITY, PROFIT GROWTH, STRUKTUR MODAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP EARNINGS QUALITY DI MASA PANDEMI COVID-19: STUDI EMPIRIS PADA PERUSAHAAN SEKTOR PERINDUSTRIAN YANG TERDAFTAR DI BEI - Ahmad, Efendi Khoeri; Sasongko, Noer (LPPM Universitas Bina Bangsa, 2024)
Earnings quality is the determination of earnings information in reflecting the company's actual performance and how reliable it is to predict the company's future performance reported in the financial statements. This study aims to analyze the effect of growth opportunity, profit growth, capital structure, and institutional ownership on earnings quality in industrial sector companies listed on the Indonesia Stock Exchange in 2019-2022. The sampling technique used purposive sampling, so that 76 samples were obtained that met the criteria as observation units. The analysis method used is multiple linear regression analysis. The results provide empirical evidence that growth opportunity and capital structure affect earnings quality. Meanwhile, profit growth and institutional ownership have no effect on earnings quality